Global Sustainable Development Evaluation Methods With Multiple-Dimensional: Sustainable Development Index - Peng, Yixiao; Zhang, Hejie (Frontiers in Environmental Science, 2022)
Sustainable development has become a new goal of world development, and the measurement of sustainable development level is an important issue. This paper introduces indicators of land ecology and allocation to establish a sustainable development index (SDI) including two levels of indicators. Based on the data research of SDI 2019 of 188 countries (regions), we conclude as follows: (1) The ranking of oil-producing countries fell sharply because of land ecological deterioration and single industrial structure; (2) The ranking of Southeast Asian and East African countries (regions) progress because of land ecological protection; (3) Most developing countries (regions) have excellent performance on land ecological protection, the main reason for changing their ranking is the inequality of land allocation. Emerging countries, such as China and Russian, also have these problems in their rapid development. We suggest that countries (regions), especially countries (regions) that rely heavily on resource extraction, should pay attention to land ecological protection, and developed and emerging countries (regions) should optimize land allocation. The main contri-bution of this paper is to provide a new solution and ideas for the measurement of sustainable development by introducing in-dicators of land ecology.